Numerical optimisation of damage in extrusion processes - Guhr, Fabian; Gitschel, Robin; Barthold, Franz-Joseph; Tekkaya, A. Erman (Technische Universität Dortmund, 2023)
Numerical optimisation is applied to rod extrusion in order to generate optimal parameter sets which result in reduced damage accumulation. A brief overview of academic applications for damage optimisation is given. Their restrictions are reflected upon, leading to the proposed framework utilising the commercial software Abaqus FEA, which enables optimisation of industrial problems with frictional contact. The framework is setup modularly to enable arbitrary choices of design variables, such as geometric parameters, and process parameters like friction coefficients or boundary conditions. The optimisation strategy is applied to forward hollow extrusion. Compared to forward rod extrusion, an additional design variable, that is, the mandrel radius, is introduced into the forming process, which increases the design space.
Proceedings in applied mathematics and mechanics; 23(3)
Keywords: 690